1967
DOI: 10.1111/j.1365-2621.1967.tb09692.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Properties of Post‐Mortem Muscle. 4. Effect of Temperature on Adenosine Triphosphate Degradation, Isometric Tension Parameters, and Shear Resistance of Bovine Muscle

Abstract: SUMMARY– Investigations were conducted on the effect of three storage temperatures, 2°, 16°, and 37°, on the changes and relationships of certain chemical and physical properties of post‐mortem bovine semitendinosus and psoas muscle. Post‐mortem muscle shortening was measured with the isometer. Isometric tension development was maximal at 2°, minimal at 16°, and at 37° tension was approximately one‐half that developed at 2°. The large tension development at 2° very likely originates from the same events as tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

1969
1969
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 19 publications
3
36
1
Order By: Relevance
“…Similarly, since post-mortem shortening of bovine muscle is greatest at 2" and least at 16" (Busch et al, 1967) and since myofibrillar protein solubility of bovine muscle at these two post-mortem storage temperatures is almost identical, it would appear that there also is no direct relationship between sarcomere length and myofibrillar protein solubility. Again, this conclusion is substantiated by the similar myofibrillar protein solubility of the psoas (average sarcomere length of 3.8 p) and the semitendinosus (average sarcomere length of 2.4 p) (Herring et al, 1965).…”
Section: Viscositymentioning
confidence: 88%
See 3 more Smart Citations
“…Similarly, since post-mortem shortening of bovine muscle is greatest at 2" and least at 16" (Busch et al, 1967) and since myofibrillar protein solubility of bovine muscle at these two post-mortem storage temperatures is almost identical, it would appear that there also is no direct relationship between sarcomere length and myofibrillar protein solubility. Again, this conclusion is substantiated by the similar myofibrillar protein solubility of the psoas (average sarcomere length of 3.8 p) and the semitendinosus (average sarcomere length of 2.4 p) (Herring et al, 1965).…”
Section: Viscositymentioning
confidence: 88%
“…Bovine muscle stored at 37" is considerably more tender at 12 hr post-mortem than muscle stored at either 2" or 16" for a similar period (Busch et al, 1967), but this increased tenderness is not accompanied by an increase in myofibrillar protein solubility at 37"; indeed solubility in 1.1 M KI actually decreases at 37".…”
Section: Viscositymentioning
confidence: 96%
See 2 more Smart Citations
“…Despite the impressive amount of research concerning proteolysis, little relationship has been found between extent of proteolysis and tenderness in either beef (Husaini et al, 1950a,b;Wierbicki et al, 1956;Locker, 1960;Davey et al, 1966) or poultry (Miller et al, 1965), although Khan et al (1964) suggested that proteolysis affects tenderness. Storage at 2" and 16" has a profound effect on postmortem muscle shortening (Locker et al, 1963 ;Busch et al, 1967) and post-mortem tenderization (Busch et al, 1967). However, post-mortem storage at these two temperatures apparently does not affect the rate of ATP degradation and pH decline (Cassens et al, 1966 ;Busch et al, 1967)) protein solubility (Chaudhry et al, 1969)) or ATPase activity of myofibrils prepared from post-mortem muscle (Go11 et al, 1967;Robson et al, 1967).…”
Section: Introductionmentioning
confidence: 95%